Assistance in the Sales Strategy of "Rainbow Pancakes" Product Innovation in Sumenep Regency - Izzatul Eriliyah; Aprilya Dwi Yandari; Isnani Yuli Andini; Miftahol Arifin; Syahril (Jurnal Pengabdian Masyarakat Bestari, 2023)
Population growth is not proportional to economic growth. Difficult job opportunities are a hope for some people for creativity, innovation or ideas to seek opportunities and even create new jobs. In this activity the service team provides assistance related to product innovation and sales strategies that can affect the development of a business home very rapidly. The methods used include planning, testing, product revision, and field testing. So that the existence of this assistance is very beneficial for the owners and employees of these business actors in terms of knowledge of marketing strategies and being able to provide a responsibility related to a good market. In addition, the dedication team provides direction for the continuation of this activity in the process of assisting in the preparation of financial reports so that the business becomes a more competitive business and becomes a good pilot business actor in the Sumenep Regency area.